Coherent Anti‐Stokes Emission from Gold Nanorods and its Potential for Imaging Applications. Issue 9 (6th May 2013) - Jiang, Li; Schie, Iwan W.; Qian, Jun; He, Sailing; Huser, Thomas
Abstract We used coherent anti‐Stokes scattering (CAS) to characterize individual gold nanorods (GNRs) and GNR aggregates. By creating samples with different densities of GNRs on silicon wafer substrates, we were able to determine surface coverage by scanning electron microscopy (SEM) and then correlate the coverage to the CAS intensities of the samples. The observed CAS signal intensity was quadratically dependent on the number of particles. We also examined the CAS signal as a function of the excitation polarization and found that the strongest signals in regularly oriented GNRs were observed when the beam polarization was aligned with the longitudinal axis of the GNRs. Irregularly oriented GNRs exhibited a different scattering pattern to that observed for regularly oriented GNRs. The polarization‐dependent scattering from oriented GNRs showed cos6 (θ) behavior. By imaging nanoscale‐sized GNR patterns using CAS and evaluating the results with SEM, we show that CAS can be used for efficient, label‐free imaging of nanoscale metallic particles.